Treatment of phthiriasis palpebrarum and crab louse: Petrolatum jelly and 1% permethrin shampoo - Karabela, Yunus; Yardımcı, Gürkan; Yıldırım, Işık; Atalay, Eray; Karabela, Şemsi Nur (Hindawi Publishing Corporation, 2015)
Phthiriasis palpebrarum is an uncommon cause of blepharoconjunctivitis in which Pthirus pubis infest the eyelashes. We report a case of unilateral phthiriasis palpebrarum with crab louse. A 45-year-old man presented with conjunctival hyperaemia and moderate itching associated with irritation, and crusty excretions of the eyelashes in the left eye. Careful slit-lamp examination revealed many lice and nits in left eye and mild conjunctival hyperaemia. No abnormality was found in the right eye. On dermatologic examination, only one louse was found at the pubic area. The patient was treated effectively with petrolatum jelly (Vaseline) and 1% permethrin shampoo (Kwellada 1% shampoo). At the end of the firstweek no louse or nitwas present on eyelashes and pubic area.
WOS: 000215278400032
PubMed ID: 26451147
Keywords: Treatment of Phthiriasis; Palpebrarum; Permethrin Shampoo